Implementasi Algoritma Genetika untuk Optimasi Penempatan Kapasitor Shunt pada Penyulang Distribusi Tenaga Listrik - Carwoto Carwoto (Universitas Stikubank, 2007)
Genetic Algorithm is a kind of search algorithm based on the mechanics of natural selection and genetics. This algorithm can search for a global optimum solution using multiple path and treat integer problem naturally. This paper presents application of Genetic Algorithm for determining the size, location, type, and number of capacitors to be placed on radial distribution system. The objective is to minimize the peak power losses and energy losses in the distribution system considering the capacitor cost. The algorithm was implemented in Delphi programming language and tested for a realistic physicallyexisting feeder to show its feasibility and capabilities.